Anisotropic spin-density distribution and magnetic anisotropy of strained La1−xSrxMnO3 thin films: angle-dependent x-ray magnetic circular dichroism - Shibata, Goro; Kitamura, Miho; Minohara, Makoto; Yoshimatsu, Kohei; Kadono, Toshiharu; Ishigami, Keisuke; Harano, Takayuki; Takahashi, Yukio; Sakamoto, Shoya; Nonaka, Yosuke; Ikeda, Keisuke; Chi, Zhendong; et al. (npj quantum materials, 2018)
Magnetic anisotropies of ferromagnetic thin films are induced by epitaxial strain from the substrate via strain-induced anisotropy in the orbital magnetic moment and that in the spatial distribution of spin-polarized electrons. However, the preferential orbital occupation in ferromagnetic metallic La 1− x Sr x MnO 3 (LSMO) thin films studied by x-ray linear dichroism (XLD) has always been found out-of-plane for both tensile and compressive epitaxial strain and hence irrespective of the magnetic anisotropy. In order to resolve this mystery, we directly probed the preferential orbital occupation of spin-polarized electrons in LSMO thin films under strain by angle-dependent x-ray magnetic circular dichroism (XMCD). Anisotropy of the spin-density distribution was found to be in-plane for the tensile strain and out-of-plane for the compressive strain, consistent with the observed magnetic anisotropy. The ubiquitous out-of-plane preferential orbital occupation seen by XLD is attributed to the occupation of both spin-up and spin-down out-of-plane orbitals in the surface magnetic dead layer. Magnetic anisotropy: spatial anisotropy of spin-polarized electrons probed Enabled by an angular dependent magneto-optical technique, the orbital states of spin-polarized electrons in La 1-x Sr x MnO 3 thin films are directly probed. Goro Shibata from University of Tokyo and colleagues in Japan use an angular dependent x-ray magnetic circular dichroism (XMCD) technique to study the magnetic anisotropy of epitaxial La 1− x Sr x MnO 3 (LSMO) thin films grown on SrTiO 3 (STO) or LaAlO 3 (LAO) substrate. The different substrates provide either tensile (STO) strain or compressive (LAO) strain. The strain modifies the orbital shapes of the spin-polarized electrons in LSMO layer, which can be directly probed by XMCD. The results show that the LSMO thin film under tensile (compressive) strain has in-plane (out-of-plane) spin-density distribution, which can be attributed to the preferential occupation of out-of-plane spin states at the surface. This helps to understand the strain controlled magnetic anisotropy in related materials.